Risk factors of cognitive impairment: Impact of decline in oral function - Toshihito Takahashi; Kodai Hatta; Kazunori Ikebe (Elsevier, 2023)
Cognitive impairment and subsequent dementia are the major causes of disability and need for nursing care among older people in worldwide. The purpose is to review well-known risk factors for cognitive impairment and dementia, focusing on the relationship between decline in oral function and current prevention strategies. Various non-modifiable and modifiable risk factors are related to cognitive impairment. Effects of oral function to cognitive impairment is not yet well recognized in the medical community, although masticatory function, occlusal force, and number of teeth have been reported to be related to cognitive function. Furthermore, occlusal force rather than number of teeth was significantly related to the early stages of cognitive impairment, and that a decline in occlusal force seemed to lead to cognitive impairment directly and indirectly through dietary intake. This relationship was significant only for occlusal force, which may be associated with the early stages of cognitive decline. Nutritional change caused by reduced masticatory function is suggested as a possible explanation. Therefore, rehabilitation or maintenance of oral function should be sought to prevent cognitive impairment.